2012
DOI: 10.1103/physreva.86.043421
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing strong-field-induced molecular vibration with femtosecond pulse shaping

Abstract: This work investigates the utility of femtosecond pulse shaping in increasing the efficiency of Raman excitation of molecules in the strong-field interaction regime. We study experimentally and theoretically the effect of pulse shaping on the strength of non-resonant coherent anti-Stokes Raman scattering in iodine vapor at laser intensities exceeding 10 13 W/cm 2 . We show that unlike the perturbative case, shaping strong non-resonant laser pulses can increase the signal strength beyond that observed with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…A similar beating phenomenon to the one described here was observed experimentally by Ohmori et al [15], (see also [16]) where a strong delayed near-infrared excitation pulse, analogous to our second excitation pulse, was seen to cause beatings in the populations of individual vibrational levels belonging to the B-state of diatomic iodine, due to the interference between the elastic |v → |v → |v Rayleigh scattering and the inelastic |v ± 1 → |v → |v Raman scattering.…”
Section: Results and Analysissupporting
confidence: 88%
“…A similar beating phenomenon to the one described here was observed experimentally by Ohmori et al [15], (see also [16]) where a strong delayed near-infrared excitation pulse, analogous to our second excitation pulse, was seen to cause beatings in the populations of individual vibrational levels belonging to the B-state of diatomic iodine, due to the interference between the elastic |v → |v → |v Rayleigh scattering and the inelastic |v ± 1 → |v → |v Raman scattering.…”
Section: Results and Analysissupporting
confidence: 88%
“…35 and is obtained at a negative chirp of φʺ ≃ −430 fs 2 and at the excitation wavenumbers of ≃ 19,660 cm −1 and ≃ 19,150 cm −1 (see Figure 2b). The enhancement of the vibrational coherence in the ground states therefore responds basically to the same phenomena that the one for the ground state population, i.e., the pump-dump intra-pulse mechanisms are promoted for negatively chirped pulses and suppressed for positive chirp.…”
Section: Main Results Obtained From the Simulationsmentioning
confidence: 99%
“…Closed-loop learning algorithms are exploited in CC to generate complex optical phases in order to optimize specific reaction pathways. CC has been used as a tool in the control of dynamic processes [17][18][19][20][21], and it explains how a specific state can be selectively populated, for example, to attain 100% population transfer [22][23][24][25], and recent studies have shown the possibility of having enhancements even higher than 100% [26][27][28][29][30][31][32][33][34][35]. QCS also exploits tailored excitation but differs from CC in its applications [30,36].…”
Section: Introductionmentioning
confidence: 99%
“…This chirped-PAP was also used to create superpositions of states in potassium atoms (Zhdanovich et al, 2009). However, attempts to implement the PAPscheme in a molecule have hitherto failed (Bitter et al, 2012). A recent proposal (Shore et al, 2016) suggests an implementation of a PAP analog in polarization optics, see Sec.…”
Section: F Hyper-raman Stirap (Stihrap)mentioning
confidence: 99%